Metformin Ameliorates Synaptic Defects in a Mouse Model of AD by Inhibiting Cdk5 Activity - Wang, YaLi; Zhao, JianHua; Guo, Fang-Li; Gao, XiaHuan; Xie, Xine; Liu, ShouQing; Yang, Xin; Yang, XinFeng; Zhang, LuYi; Ye, YuXiao; Fan, LiBing; Wang, JianGang (Frontiers in Cellular Neuroscience, 2020)
Cyclin-dependent kinase 5 (Cdk5) is a serine/threonine kinase that is activated by the neuron specific activators p35/p39 and plays important roles in neuronal development, synaptic plasticity and cognitive behavior. However, proteolytic cleavage of p35 to p25 leads to prolonged and aberrant Cdk5 activation and results in synaptic depression, highly mimicking the early pathology of several neurodegenerative diseases, including Alzheimer’s disease (AD) and Parkinson’s disease (PD). Therefore, Cdk5 inhibition is a potential promising strategy for AD drug development. Here in the present study, we show that metformin, the most widely used drug for type 2 diabetes, suppresses Cdk5 hyper-activation and Cdk5-dependent tau hyper-phosphorylation by decreasing p25 overproduction in APP/PS1 mouse hippocampus. Moreover, chronic metformin treatment rescues core phenotypes in APP/PS1 mice, as evidenced by restored spine density, surface GluA1 trafficking, LTP expression and spatial memory. Taken together, our study discovers an unanticipated role of metformin in alleviating AD pathogenesis and suggests metformin is a potential AD therapeutic.